Distinguishing Homokaryons and Heterokaryons in Medicinal Polypore Mushroom Wolfiporia cocos (Agaricomycetes) Based on Cultural and Genetic Characteristics - Li, Shoujian; Wang, Qi; Dong, Caihong (Frontiers in Microbiology, 2021)
The sclerotia of Wolfiporia cocos are a kind of traditional medicine and food with excellent benefits and are widely used in China, Japan, and other Asian countries. The mating system of fungi is not only of practical importance for breeding but also has profound effects on genetic variability and molecular evolution. However, the lack of clamp connections in W. cocos increases the difficulty of research on mating systems. In this study, homokaryon and heterokaryon were distinguished by comparing the characteristics of culture, fruiting tests, and molecular markers, which was further demonstrated by k-mer analysis based on Illumina sequencing. Basidiospores of W. cocos with uninucleate, binucleate, and nuclear-free were observed, and binucleate basidiospores predominated. Brown-type colonies, slow growth rates in both PDA medium and sawdust substrate, and neutral pH after the growth of mycelia and fruiting were found to be morphological and growth characteristics of homokaryotic strains. Primers SSR37 and 38 were screened to identify homokaryons. K-mer analysis based on Illumina sequencing exhibited different heterozygous ratios for homokaryons and heterkaryons. The results revealed that the predominant mating system of W. cocos of Chinese population was pseudo-homothallism, and heterothallism also existed in all probabilities. This study will be helpful for the cross-breeding of this precious medicinal mushroom and for understanding the evolution and population structure.